An Economic Analysis of Direct Costs of Distal Radius Fixation and the Implications of a Disposable Distal Radius Kit. Issue 9 (September 2021) - Lans, Jonathan; Westenberg, Ritsaart F.; Verhiel, Svenna H.W.L.; Garg, Rohit; Jupiter, Jesse B.; Chen, Neal C.
Abstract : Objective: To assess the direct costs of distal radius fracture volar plate (VP) fixation and to create a model to examine the effect of these cost drivers. Materials and Methods: Retrospectively, 744 distal radius fractures treated with open reduction and internal fixation (ORIF) were identified. The outcomes assessed included (1) the direct costs related to distal radius ORIF and (2) if a VP alone was amenable. Costs were represented as a cost ratio relative to the average cost of distal radius ORIF, where the average value is set as 1.0. Simulation models were run with all cost drivers (sex, age, open fracture, intra-articular fracture, and ancillary fixation) and with only ancillary fixation as a cost driver. Results: The cost ratio ranged from 0.61 to 1.81 and ancillary fixation was associated with increased implant costs in multivariable analysis. In the simulations, the cost ratio ranged from 0.96 to 1.23 when all cost drivers were included and from 0.99 to 1.20 if only ancillary fixation was included as a cost driver, a reduction of the range by 22.2%. Older patients, females, closed fractures, and extra-articular fractures were more amenable to VP fixation alone. Conclusions: Eighty-three percent of the surgically treated distal radius fractures were treated with VP fixation alone. A disposable kit could help limit cost variance per case by roughly 22%, as only ancillary fixation varies these costs. Closed fractures and extra-articular fractures in older patients or female patients are more amenable to VP fixation alone. Level of Evidence: Economic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.